L'analyse log-linéaire de tableaux de contingence et le modèle logit II : interaction et rapport de chances à propos d'un problème d'évaluation contingente - Estelle Kah (Unité Mixte de Recherche 8504 Géographie-cités, 2003)
In this second part of the presentation of the loglinear analysis and the logit model, the author shows, within the frame of a contingent valuation, a few examples of answers to hypotheses about relations between the acceptation to pay more for household waste service in order to ensure a long term environment protection, and the basic geographical context, the level of education, the level of income, as well as sorting behaviour, which constitute the features whose interactions we want to unveil through the methods described in the first text.